مساهمة حوكمة المؤسسات في تحقيق جودة المعلومة المحاسبية - زعرور, نعيمة; سعدي, عبد الحق (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة الى توضيح مساهمة حوكمة المؤسسات في تحقيق جودة المعلومة المحاسبية، وذلك من خلال التطرق الى الاطار النظري لكل من حوكمة المؤسسات وجودة المعلومة المحاسبية وابراز العلاقة القائمة بينهما، وذلك باستخدام المنهج الوصفي، أما فيما يخص الدراسة الميدانية تم الاعتماد على المنهج الوصفي التحليلي، وذلك باستخدام أداة الاستمارة وتم توزيعها على مجموعة من المؤسسات بولاية بسكرة، حيث بلغت نسبة الاستمارات المسترجعة (61 استمارة)، وأستخدم البرنامج الاحصائي (19spss) لتحليلها. وقد خلصت هذه الدراسة إلى جملة من النتائج أهمها: أن الالتزام بتطبيق مبادئ حوكمة المؤسسات يؤدي إلى المزيد من الإفصاح والشفافية في إعداد التقارير المالية للمؤسسات. This study aims to clarify the contribution of corporate governance to achieving the quality of accounting information, by looking at the theoretical framework for both corporate governance and the quality of accounting information and highlighting the relationship between them, using the descriptive approach. As for the field study, reliance was taken on the descriptive analytical approach, Using the form tool, it was distributed to a group of institutions in the state of Biskra, where the proportion of retrieved forms reached (61 forms), and the statistical program (19spss) was used for analysis. This study has reached a number of results, the most important of which are: The commitment to apply the principles of corporate governance leads to more disclosure and transparency in preparing financial reports for institutions.
Keywords: حوكمة المؤسسات، معلومة محاسبية، جودة معلومة محاسبية